2022
DOI: 10.2196/32215
|View full text |Cite
|
Sign up to set email alerts
|

Implementation Frameworks for Artificial Intelligence Translation Into Health Care Practice: Scoping Review

Abstract: Background Significant efforts have been made to develop artificial intelligence (AI) solutions for health care improvement. Despite the enthusiasm, health care professionals still struggle to implement AI in their daily practice. Objective This paper aims to identify the implementation frameworks used to understand the application of AI in health care practice. Methods A scoping review was conducted using t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
55
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 96 publications
(59 citation statements)
references
References 48 publications
4
55
0
Order By: Relevance
“…The conclusion in newly published reviews addressing regulation, privacy and legal aspects [ 15 , 16 ], ethics [ 16 18 ], clinical and patient outcomes [ 19 21 ] and economic impact [ 22 ], is that further research is needed in a real-world clinical setting although the clinical implementation of AI technology is still at an early stage. There are no studies describing implementation frameworks or models that could inform us concerning the role of barriers and facilitators in the implementation process and relevant implementation strategies of AI technology [ 23 ]. This illustrates a significant knowledge gap on how to implement AI in healthcare practice and how to understand the variation of acceptance of this technology among healthcare leaders, healthcare professionals, and patients [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conclusion in newly published reviews addressing regulation, privacy and legal aspects [ 15 , 16 ], ethics [ 16 18 ], clinical and patient outcomes [ 19 21 ] and economic impact [ 22 ], is that further research is needed in a real-world clinical setting although the clinical implementation of AI technology is still at an early stage. There are no studies describing implementation frameworks or models that could inform us concerning the role of barriers and facilitators in the implementation process and relevant implementation strategies of AI technology [ 23 ]. This illustrates a significant knowledge gap on how to implement AI in healthcare practice and how to understand the variation of acceptance of this technology among healthcare leaders, healthcare professionals, and patients [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…We thus do not know if these models are applicable to AI as a socio-technical system or if other determinants are important for the implementation process. Likewise, based on a new literature study, we found no AI-specific implementation theories, frameworks, or models that could provide guidance for how leaders could facilitate the implementation and realize the potential of AI in healthcare [ 23 ]. We thus need to understand what the unique challenges are when implementing AI in healthcare practices.…”
Section: Introductionmentioning
confidence: 99%
“…This could reflect a tendency to raise more ethical concerns regarding implications within these technology areas instead of genetics and gene technology, gene-based screening, and technologies used for assistance during illness and rehabilitation. It could also reflect the current hype of applying health technologies based on health care data and artificial intelligence and that these technologies are more studied in general and with low reference to actual application and empirical grounding [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…A few empirical studies with robust methodology, such as randomized controlled studies, have investigated the effects of implementation of AI technology in practice [20], but there are no AI-specific implementation theories, models, or frameworks that could provide guidance for how to translate the potential of AI into daily health care practices [22]. Thus, there is currently a paucity of knowledge concerning several key issues, including barriers and facilitators to successful implementation of AI in health care; what strategies might be used to support AI implementation; how the use of AI might change existing clinical workflows, roles, and responsibilities; or how the infrastructure of management and governance should be constructed to be effective [23].…”
Section: Introductionmentioning
confidence: 99%